Design and Build Application of Web-Based Practice Material Management Information System (SIP-BATIK JKG) in the Laboratory of the Department of Dental Health Poltekkes Ministry of Health Semarang - Saadah, Khasiah; Sunarjo, Lanny; raspin, rasipin; Fatmasari, Dyah; Djamil, Masrifan (Postgraduate Program , Poltekkes Kemenkes Semarang, 2023)
ABSTRACTThe quality of material management in the JKG Semarang laboratory has not been maximized because the material management is done manually. Manual management creates problems in management quality and user satisfaction. The SIP BATIK JKG model is an information system designed to be able to overcome problems in the laboratory. The purpose of this study is a practical material management model with SIP-BATIK JKG that is feasible and effective to improve the quality of material management and increase user satisfaction in the JKG Semarang laboratory. This study uses the R&D method, the trial model uses a pre-experimental design method with purposive sampling. The independent variable is the web-based SIP BATIK JKG model and the dependent variable includes the quality of material management and user satisfaction. Respondents were 50 people. The data from the model test used the proportion test and the different pair test. The results of expert validation using the kappa coefficient test with a value of 0.737 (k>0.6) satisfactory category means that the SIP BATIK JKG model is relevant and feasible as a material management system in the laboratory. Most of the respondents' assessments stated that the quality of SIP BATIK JKG was in the good and very good categories. The subject's ability to the quality of material management and user satisfaction after treatment increased significantly compared to before with p = 0.000. The results of the effect size test on aspects of user satisfaction (d=1.30) and materials management (d=1.26) in the strong effect category mean that the SIP BATIK JKG model is very effective in improving the quality of material management services in the JKG lab. Conclusion The application of the SIP BATIK JKG model is relevant and suitable for use in management by users to improve the quality of information systems in the JKG laboratory ABSTRAKKualitas manajemen bahan di laboratorium JKG Semarang belum maksimal karena pengelolaan bahan dilakukan secara manual. Pengelolaan secara manual menimbulkan masalah pada kualitas pengelolaan bahan dan kepuasan pengguna. Model SIP BATIK JKG merupakan sistem informasi yang dirancang untuk dapat mengatasi permasalahan manajemen bahan lab dan meningkatkan kepuasan pengguna di laboratorium. Tujuan penelitian ini Menghasilkan model manajemen bahan praktik dengan SIP-BATIK JKG yang layak dan efektif untuk meningkatkan kualitas manajemen bahan dan meningkatkan kepuasan pengguna di laboratorium JKG Semarang. Penelitian ini menggunakan metode R&D, uji coba model menggunakan metode pre-eksperimen design dengan purposive sampling. Variabel independen adalah model SIP BATIK JKG berbasis web dan variabel dependen meliputi kualitas manajemen bahan dan kepuasan pengguna. Responden sebanyak 50 orang ( 40 mahaiswa, 8 dosen dan 2 petugas laboratorium). Data hasil uji model menggunakan uji proporsi dan uji beda berpasangan. Hasil validasi ahli menggunakan uji koefisien kappa dengan value 0,737 (k>0,6) kategori memuaskan artinya model SIP BATIK JKG relevan dan layak sebagai sistem pengelolaan bahan di laboratorium. Penilaian responden sebagian besar menyatakan kualitas SIP BATIK JKG dalam kategori baik dan sangat baik. Kemampuan subjek terhadap Kualitas sistem informasi setelah perlakuan meningkat bermakna dibandingkan sebelumnya dengan p=0,000. Hasil uji effect size pada aspek kepuasan pengguna(d=1,30 ) dan manajemen bahan (d=1,26) kategori strong effect artinya Model SIP BATIK JKG sangat efektif meningkatkan kualitas pelayanan pengelolaan bahan di lab JKG. Kesimpulan Penerapan model SIP BATIK JKG relevan dan layak digunakan dalam pengelolaan bahan oleh pengguna untuk meningkatkan kualitas sistem informasi di laboratorium JKG.